Existence of a solution for a nonlinear integral equation by nonlinear contractions involving simulation function in partially ordered metric space - Lo'Lo', Parvaneh; Shams, Maryam; De la Sen, Manuel (Nonlinear Analysis: Modelling and Control, 2023)
In a recent paper, Khojasteh et al. presented a new collection of simulation functions, said Z-contraction. This form of contraction generalizes the Banach contraction and makes different types of nonlinear contractions. In this article, we discuss a pair of nonlinear operators that applies to a nonlinear contraction including a simulation function in a partially ordered metric space. For this pair of operators with and without continuity, we derive some results about the coincidence and unique common fixed point. In the following, many known and dependent consequences in fixed point theory in a partially ordered metric space are deduced. As well, we furnish two interesting examples to explain our main consequences, so that one of them does not apply to the principle of Banach contraction. Finally, we use our consequences to create a solution for a particular type of nonlinear integral equation.
Keywords: simulation functions; coincidence point; compatible; partially ordered metric space; integral equation